Pengaruh Pengawasan, Lingkungan Kerja dan Motivasi terhadap Etos Kerja Karyawan pada SPPBE PT Sumber Mutiara Lestari Kabupaten Batu Bara - Nuraini Nuraini; Muh Saleh Malawat (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Supervision, work environment, and motivation are important factors influencing employee work ethic in industrial organizations. At SPPBE PT Sumber Mutiara Lestari Batu Bara Regency, variations in employee performance indicate the need to examine these factors more systematically. This study aims to analyze the effect of supervision, work environment, and motivation on employee work ethic. Quantitative research with survey method was used. The sample consisted of 33 respondents using saturated sampling technique. Data were collected through Likert scale questionnaires. Data were processed using SPSS version 25 and analyzed using multiple linear regression. Results show that supervision work environment and motivation have a significant positive effect on employee work ethic both partially and simultaneously. The findings imply that improving supervision quality, creating a conducive work environment, and enhancing employee motivation can strengthen organizational performance at the company. Therefore managerial policies should prioritize these three factors to improve employee discipline and productivity. Overall the regression analysis confirms that all independent variables contribute meaningfully to employee work ethic in the studied organization. These results are consistent with human resource management theories emphasizing the role of leadership environment and motivation in shaping employee behavior. Future research is recommended to expand variables and samples in future.